Field evaluation of the olfactory response of Leptocorisa spp. to shrimp and invasive apple snail carcass baits - Waridha Syahrur Rahmawati; M. Bayu Mario; Nuramaliya Nuramaliya; Ravindra Chandra Joshi; Ahdin Gassa (Wallacea Plant Protection Journal, 2026)
Rice bugs (Leptocorisa spp.) are destructive agricultural pests that inflict severe damage on paddy crops from the flowering stage through the milk ripening stage. Heavy infestations often result in devastating crop failure, compromised grain quality, and reduced overall agricultural yield. To mitigate these economic losses, developing environmentally sustainable management strategies that suppress pest populations without disrupting the surrounding ecosystem is crucial. This study evaluated the field efficacy of olfaction-based traps baited with decaying animal carcasses to actively lure and capture rice bugs. The field experiment was conducted on a 30 × 15 m rice field plot cultivated with the Ciliwung Super cultivar using a direct-seeding system. The custom traps were fabricated from 1,500 mL plastic bottles, each loaded with 150 g of bait consisting of either decaying shrimp or invasive apple snail (Pomacea spp.) carcasses, with ten experimental replications per treatment. Capture rates were recorded at three-day intervals, whereas damage intensity was assessed at seven-day intervals. The experimental results demonstrated that both shrimp and invasive apple snail carcass baits effectively attracted Leptocorisa spp. adults. Although the difference was not statistically significant, shrimp carcass bait showed a numerically higher attraction rate than invasive apple snail bait, suggesting its potential as an organic attractant for rice bugs monitoring and management.